EFISIENSI KERJA CHRUSING PLANT PT. NUR HAZANAH KARYA ABADI DISTRIK PRAFI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Albertina Awom; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
This study aims to determine the efficiency of the crushing plant at PT. Nur Hazanah Karya Abadi, using a descriptive method, describes the state of the object of research directly. It is known that the average efficiency value based on the availability of mechanical equipment is effectiveness 67.8%, availability of mechanical/physical 67.15%, utility 36.5%, and optimum efficiency 34.85%. Based on the work assessment table, the crushing plant efficiency is classified as very bad, due to the optimum efficiency value below 58%.